Role of an FtsK-Like Protein in Genetic Stability in Streptomyces coelicolor A3(2) - Wang, Lei (American Society for Microbiology, 2007)
Streptomyces coelicolor A3(2) does not have a canonical cell division cycle during most of its complex life cycle, yet it contains a gene (ftsK(SC)) encoding a protein similar to FtsK, which couples the completion of cell division and chromosome segregation in unicellular bacteria such as Escherichia coli. Here, we show that various constructed ftsK(SC) mutants all grew apparently normally and sporulated but upon restreaking gave rise to many aberrant colonies and to high frequencies of chloramphenicol-sensitive mutants, a phenotype previously associated with large terminal deletions from the linear chromosome. Indeed, most of the aberrant colonies had lost large fragments near one or both chromosomal termini, as if chromosome ends had failed to reach their prespore destination before the closure of sporulation septa. A constructed FtsK(SC)-enhanced green fluorescent protein fusion protein was particularly abundant in aerial hyphae, forming distinctive complexes before localizing to each sporulation septum, suggesting a role for FtsK(SC) in chromosome segregation during sporulation. Use of a fluorescent reporter showed that when ftsK(SC) was deleted, several spore compartments in most spore chains failed to express the late-sporulation-specific sigma factor gene sigF, even though they contained chromosomal DNA. This suggested that sigF expression is autonomously activated in each spore compartment in response to completion of chromosome transfer, which would be a previously unknown checkpoint for late-sporulation-specific gene expression. These results provide new insight into the genetic instability prevalent among streptomycetes, including those used in the industrial production of antibiotics.